2021
DOI: 10.1155/2021/5541753
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrol A Attenuates Myocardial Ischemia/Reperfusion‐Induced Myocardial Apoptosis through Upregulation of 14‐3‐3θ

Abstract: Schisandrol A (SA), one of the most abundant bioactive lignans extracted from the Schisandra chinensis (Turcz.) Baill., has multiple pharmacological properties. However, the underlying mechanisms of SA in protection against myocardial ischemia/reperfusion (MI/R) injury remain obscure. The present experiment was performed to explore the cardioprotective effects of SA in MI/R injury and hypoxia/reoxygenation- (H/R-) induced cardiomyocyte injury and clarify the potential underlying mechanisms. SA treatment signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…After that, an animal model of isoproterenol-induced heart failure was successfully established. Numerous studies in the literature have shown that [9][10][11][12][13][14][15]18 mono-flavored S. chinensis as well as mono-flavored CQ10 can inhibit cardiomyocyte apoptosis and have a protective effect on cardiomyocytes. Based on this, this paper used S.chinensis in combination with CQ10 confirmed the ameliorative effect of S.chinensis in combination with CQ10 on isoproterenol-induced heart failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, an animal model of isoproterenol-induced heart failure was successfully established. Numerous studies in the literature have shown that [9][10][11][12][13][14][15]18 mono-flavored S. chinensis as well as mono-flavored CQ10 can inhibit cardiomyocyte apoptosis and have a protective effect on cardiomyocytes. Based on this, this paper used S.chinensis in combination with CQ10 confirmed the ameliorative effect of S.chinensis in combination with CQ10 on isoproterenol-induced heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…S. chinensis is a traditional northeastern authentic herb, mainly produced in Heilongjiang, Jilin, and Liaoning provinces, and is known as Schisandra because of its sweet, sour, and salty skin and pungent, bitter, and salty core. 8 Numerous experimental studies have shown that, [9][10][11][12][13][14][15] S.chinensis and its main chemical components schisandrin B, Schisanhenol, Schizandrin C and Schisandrol A can inhibit myocardial cell apoptosis, reduce myocardial cell inflammatory damage and have a cardioprotective effect.…”
Section: Introductionmentioning
confidence: 99%
“…The protein concentration was calculated using a BCA protein assay kit (P0012, Beyotime, Shanghai, China) following the manufacturer's instructions [ 24 ]. Equal amounts of total protein (40 μg) were electrophoresed on 10% SDS-PAGE gels and transferred onto PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Gong et al [ 38 ] reported that schisandrin appears to attenuate myocardial ischemia/reperfusion-induced myocardial apoptosis through upregulation of 14-3-3 θ . The authors also noted that the tested compound has antioxidant properties: it increased the activity of GSH-PX and reduced the level of MDA and reactive oxygen species (ROS).…”
Section: Cardioprotective Properties Of S Chinenis ...mentioning
confidence: 99%